2007
DOI: 10.1126/science.1139548
|View full text |Cite
|
Sign up to set email alerts
|

Legumes Symbioses: Absence of Nod Genes in Photosynthetic Bradyrhizobia

Abstract: Leguminous plants (such as peas and soybeans) and rhizobial soil bacteria are symbiotic partners that communicate through molecular signaling pathways, resulting in the formation of nodules on legume roots and occasionally stems that house nitrogen-fixing bacteria. Nodule formation has been assumed to be exclusively initiated by the binding of bacterial, host-specific lipochito-oligosaccharidic Nod factors, encoded by the nodABC genes, to kinase-like receptors of the plant. Here we show by complete genome sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
396
2
16

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 547 publications
(419 citation statements)
references
References 41 publications
5
396
2
16
Order By: Relevance
“…Except for some photosynthetic species of the genus Bradyrhizobia (Giraud et al, 2007), all bacteria described thus far as being capable of establishing a symbiosis with legumes harbour nodulation (nod) and nitrogen fixation (nif, fix) genes. This opens up the possibility of screening for these genes as an alternative to nodulation tests.…”
Section: Discussionmentioning
confidence: 99%
“…Except for some photosynthetic species of the genus Bradyrhizobia (Giraud et al, 2007), all bacteria described thus far as being capable of establishing a symbiosis with legumes harbour nodulation (nod) and nitrogen fixation (nif, fix) genes. This opens up the possibility of screening for these genes as an alternative to nodulation tests.…”
Section: Discussionmentioning
confidence: 99%
“…Some divergent Bradyrhizobium spp. (e.g., BTAi1 and ORS278) lack a symbiosis island and use a different mechanism to nodulate hosts [41]. Previous studies have revealed that Bradyrhizobium populations can exhibit patterns consistent with epidemics such as a few genotypes existing at high frequency at a single site [33] or genotypes isolated at multiple locations [34,35,37].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, no symbiosis island containing nif/fix and nod genes has been found on the genomes of Rhodopseudomonas palustris (Larimer et al, 2004) or Bradyrhizobium sp. BTAi1 and ORS278 (Giraud et al, 2007), although BTAi1 and ORS278 are stem-nodulating and nitrogen-fixing bacteria (Giraud et al, 2007). When we examined the relatedness of the core genomic regions outside the symbiosis island by principal component analysis, non-Bj strains, except for B. elkanii USDA76, formed a compact cluster (Figure 2b).…”
Section: Cgh Profiles Of Non-bj Strainsmentioning
confidence: 99%
“…Members of Bradyrhizobiaceae include a number of nonsymbiotic bacteria with diverse biochemical functions such as photosynthesis (Molouba et al, 1999;Larimer et al, 2004;Giraud et al, 2007), oligotrophy (Saito et al, 1998;King, 2007), 2,4-dichlorophenoxyacetic acid degradation (Kamagata et al, 1997) and nitrification (Starkenburg et al, 2006).…”
Section: Introductionmentioning
confidence: 99%